A chart illustrative of the cruise of the American Arctic expedition in search of Sir John Franklin, in the years 1850 & 1851 : fitted out by Henry Grinnell Esq. of New York, commanded by E.J. DeHaven, Lieut. U.S. Navy / compiled by Geo. P. Welsh - United States Hydrographic Office (Distrurnell & Schroeter, 1853)
“From materials in the Bureau of Ordnance and Hydrography, Commodore Lewis Warrington, Chief of Bureau.” Map listed in: Manuscript and annotated maps in the American Geographical Society Library: a cartobibliography, 2010. Color; 1:5,000,000